Flow-through laminar anodes with variable interlaminar distance to modulate the current density of urine-fed bio-electrochemical systems - Prudente, Mariano (2023)
Three-dimensional (3D) porous anodes used in urine-powered bio-electrochemical applications usually lead to the growth of electro-active bacteria on the outer electrode surface, due to limited microbial access to the internal structure and lack of permeation of culture medium through the entire porous architecture. In this study, we propose the use of 3D monolithic Ti4O7 porous electrodes with controlled laminar structures as microbial anodes for urine-fed bio-electrochemical systems. The interlaminar distance was tuned to modulate the anode surface areas and, thus, the volumetric current densities. To profit from the true area of the electrodes, urine feeding was performed as a continuous flow through the laminar architectures. The system was optimized according to the response surface methodology (RSM). The electrode interlaminar distance and the concentration of urine were selected as independent variables, with the volumetric current density as the output response to optimize. Maximum current densities of 5.2 kA.m− 3 were produced from electrodes with 12 µm-interlaminar distance and 10 %v/v urine concentrations. The present study demonstrates the existence of a trade-off between the accesibility to the internal electrode structure and the effective usage of the surface area to maximize the volumetric current density when diluted urine is used as flowing-through feeding fuel.